Glacial, fluvial and volcanic landscape evolution in the Laguna Potrok Aike maar area, Southern Patagonia, Argentina - Coronato, Andrea Maria Josefa (2013)
We describe the Pleistocene evolution of the landscape in the Laguna Potrok Aike area in southern Patagonia, Argentina, based on a geomorphological survey. Basaltic eruptions generated tablelands and scoria cones between the Late Miocene and Middle Pleistocene, and phreatomagmatic eruptions produced maars during Middle and Late Pleistocene time. The first glaciations during the Early Pleistocene generated a gently undulating to flat landscape that was affected by cryogenic processes; they are documented but not dated. Outwash surfaces indicate that the Greatest Patagonian Glaciation was multi-phased. The eruption that produced Potrok Aike maar truncated terrace levels dating to a Middle Pleistocene glaciation. The abundance of maars dating to this time may be linked to large amounts of water associated with meltwater streams and permafrost. The landscape in the Potrok Aike area has changed little since the Middle Pleistocene and only minor modifications of landforms have occurred due to cryogenesis, moderate fluvial incision, mass wasting and eolian activity.